The relationship between knowledge, awareness, perceptions of mses on compliance with the halal process with self-declared as a moderating variable - Emul Mulyana; Enjat Sudrajat; Meri Lustianah; Masitoh Masitoh (International Journal of Applied Finance and Business Studies, 2023)
Indonesia is ranked fourth in the world's halal product players, even though Indonesia has the largest Muslim population. The study aims to determine whether there is an effect of knowledge on compliance with the Halal Product Process (PPH) for Micro and Small Enterprises (MSEs). To find out whether awareness affects PPH compliance, does perception affect PPH compliance. Updates in this study include self-declare as a moderating variable on the relationship between knowledge and compliance, as a moderating variable on the relationship between awareness and compliance, as a moderating variable for the influence of perceptions on PPH compliance. The research was conducted on 400 small and medium enterprises (MSEs) in Banten province. This research is a quantitative research with a casual descriptive approach and was processed using PLS software version 4.0, indicating a positive effect of knowledge on PPH compliance. There is a positive influence between awareness on PPH compliance. There is a positive influence on perceptions on PPH compliance. Meanwhile, the self-declared hypothesis which moderates the three relationships above, none of which can be accepted